Mine to Win, 2016, by Hiwot Taffera - Netsanet Gebremichael (Journal of Ethiopian Studies, 2025)
A theoretical discussion of literature, popular memory, and history enables us to argue that novels are valid historical sources, pertinent to their role in shaping popular memory and imagination. The employment of memory and imagination is the work of both historians and novelists. Bearing in mind the role of literary texts in the “deployment of popular memory to recompose past events,”  the historian uses novels for their role in crafting collective popular imagination rather than for their accurate historical information.  Although not accurate, the novel can provide an insight into the social and cultural aspects of human life. Literary works are not a reliable source of information about past events.  However, art forms such as the novel take a historical theme to construct their imaginative story. By refocusing the debate on history in literature from the accuracy of information to the role of literature informing national imagination and popular memory, novels can be sites for shaping popular perception and exploring historical themes. Similarly, the novel Mine to Win imaginatively reconstructs a periodized past of the 1850s-1870s, revolving around student life, scholarly traditions of that epoch, and the everyday lives of the community.